Analysis of Positive Law on the Origin of Children from Fasid Marriage: Case Study of Stipulation No. 040/Pdt.P/2017/Pa.Sal in Salatiga Religious Court - Tegus Basuki (QURU’: Journal of Family Law and Culture, 2024)
Every child has the right to know his or her parents, to be raised, and to be cared for by his or her own parents. The provision regarding the child's right to know who his or her parents are, in the sense of origin (including the mother of the milk), is intended to avoid the disconnection of genealogy and blood relations between the child and his or her biological parents, while the right to be raised and cared for by his or her parents is intended so that the child can obey and respect his or her parents. This statement is in accordance with Article 7 Paragraph 1 of Law of the Republic of Indonesia Number 23 of 2002 concerning Child Protection. This research focuses on the position of children born from a fasid marriage, do they still have the right to know their parents and are considered legitimate children? This research is the result of Library Research and Field Research which is Comparative Descriptive. The approach that researchers use is the Normative Juridical approach. This study aims to answer the problem of whether children born from a broken marriage or called fasid can be considered a legitimate child, or only considered to be a biological child and how the consideration of the panel of judges examining case Number: 040/Pdt.P/2017/PA.Sal in deciding the case. The result of this study is that the author sees that the consideration of the judges in deciding refers to the decision of the Constitutional Court Number 46/PUU-VIII/2010 dated 27 February 2010, Article 43 Paragraph 1 of Law Number 1 of 1974 which states, "Children born outside marriage only have a civil relationship with their mother and their mother's family", does not have binding legal force as long as it is interpreted to eliminate civil relationships with men who can be proven based on science and technology and / or other evidence according to the law turns out to have a blood relationship as the father.